THE FIRST CASE OF GUSELKUMAB-INDUCED THYROID STORM IN A YOUNG WOMAN WITH PLAQUE PSORIASIS - Rofii, Nursafinas; Ng, Ooi Chuan; Ng, Jo-An (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION/BACKGROUND Guselkumab is a biologic agent used to treat moderate to severe plaque psoriasis by targeting interleukin-23 (IL-23). While effective in managing psoriasis, the impact of Guselkumab on thyroid function is not well-documented. Autoimmune thyroid diseases such as Graves’ disease can be triggered by several factors, including immune-modulating therapies. This case report aims to highlight a rare but severe adverse reaction of Guselkumab in a young female with a predisposition to autoimmune diseases. CASE We report a 20-year-old Malay female, a medical student, with plaque psoriasis on Guselkumab therapy. Her elder sister has psoriasis, Graves’ disease with severe orbitopathy. Following the patient’s first injection of Guselkumab, she developed a moderate-sized diffuse goiter with tenderness. Despite this, she continued with two more doses of Guselkumab over the next six months at three-month intervals. Approximately two weeks after the fourth dose of Guselkumab, she experienced symptoms of palpitations, hand tremors, low-grade fever, and generalized malaise. She was admitted to the hospital for treatment of severe thyrotoxicosis. Serum free T4 levels were found to be three times above the upper limit of normal, T4: 59.1 pmol/l and a TSH level of <0.01 mIU/l with borderline high anti-TPO antibodies. Despite good compliance with carbimazole 30 mg daily and propranolol 60 mg three times daily for one month, her condition worsened. Development of signs of thyroid storm, including anxiety, hyperdefecation, hand tremor, low-grade fever (37.6 °C), and sinus tachycardia (150 beats per minute) prompted consult at the emergency department, where she was found to have Burch-Wartofsky Point Scale of 45. Acute phase reactants showed a CRP level of 5, which made subacute thyroiditis unlikely. Due to the severity of her condition, Lugol’s iodine was administered, thus precluding the performance of thyroid scintigraphy. Neck ultrasound revealed features suggestive of thyroiditis in which Graves’ disease cannot be excluded, with no focal lesion of thyroid parenchyma found. During the admission, response to intravenous hydrocortisone 100 mg tds and high dose propylthiouracil 250 mg QID was slow, thus necessitating alternative treatment with T. cholestyramine 1 g QID. Her TSH level remained static at <0.01 mIU/l and free T4 decreased from >64 pmol/l to 54.5 pmol/l then to 32.2 pmol/l. She subsequently underwent a total thyroidectomy for severe Graves’ disease with grade 3 goiter. The postoperative course was complicated by transient hypocalcemia requiring calcium and vitamin D supplementation. Psoriasis remained well-controlled but a flare developed postoperatively, prompting the reintroduction of Guselkumab. CONCLUSION This case underscores the importance of monitoring thyroid function in patients receiving biologic agents, especially in those with a known predisposition to autoimmune diseases. Clinicians should remain vigilant for signs of thyroid dysfunction and consider the potential of biologic agents like Guselkumab to trigger severe autoimmune reactions, including thyroid storm. Early surgical intervention enabled optimal treatment of the skin disorder while preventing further life-threatening complications.